Audit Attributes and Financial Reporting Quality in Nigeria: Evidence from Deposit Money Banks - Majeed Ajibola Ibrahim; Adedeji Daniel Gbadebo (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: The issue of high-quality financial reporting is of concern to financial report users and the entire economy since it influences financial decisions. This paper examines the relationship between audit attributes and the financial reporting quality of deposit money banks (DMBs) in Nigeria. Method: The paper applied the Generalized Least Square (random effects) regression to analyze how audit fees, audit firm independence, auditor tenure, and other controlled variables affect the quality of financial reporting of DMBs during 2014–2022. Results: The findings reveal that the main variables—audit fees, auditor tenure, and audit firm independence: have positive and significant impacts on financial reporting quality. Specifically, a unit change in audit fees, auditor tenure, and audit firm independence increases earnings quality by 0.104, 0.081, and 0.223, respectively. When client asset size, audit firm type, and firm growth are controlled for, they also exert positive and significant effects on financial reporting quality. Implications: The findings have implications for DMBs, capital market stakeholders, and the broader economy. The study recommends measures to ensure enhanced financial reporting quality for Nigerian DMBs, including the need for management and regulatory bodies to place strong emphasis on the independence of audit firms in all facets of auditors’ work. Novelty: This study contributes to the financial reporting literature by empirically demonstrating how specific audit attributes improve financial reporting quality in Nigeria’s banking sector, offering evidence from a developing economy context that has been underexplored in prior research.